Foodocracy and the Politics of Radical Care in The Black Soil - Dwivedi, Om Prakash (SARE: Southeast Asian Review of English, 2023)
The paper examines the extractive forces that systematically erode the life conditions of the citizens of Perumalpuram village. Deprived of any rights, even the right to be identified as humans, the villagers are treated as wasted lives, good enough only to work without any monetary benefit, on the farms owned illegally by the village head, Sarkaraisamy, also known as the Master. Focussing on the food shortage and lack of affective bonds, the paper advocates a turn from governmentality to caremenatlity, the base of which is the creation, recognition, and promotion of foodocracy and networks of care. It identifies foodocracy as a reformative movement, exposing the structural inequity and disfranchisement and leading to enhanced vulnerability in Perumalpuram and the surrounding regions. That foodocracy should not be limited to this village but become a zeitgeist in the global fight for equal access to food is the central argument of this paper. That is to say, this paper underlines the need to make foodocracy a global movement for collective survival.